2005
DOI: 10.1038/sj.onc.1209137
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic repression of RASSF1A but not CASP8 in supratentorial PNET (sPNET) and atypical teratoid/rhabdoid tumors (AT/RT) of childhood

Abstract: Supratentorial primitive neuroectodermal tumors (sPNET) and atypical teratoid/rhabdoid tumors (AT/RT) of the CNS represent a biological and clinical enigma, despite advances in both molecular techniques and clinical management for these two rare embryonal brain tumors of childhood. Epigenetic changes hold great potential as possible disease mechanisms and may be manipulated therapeutically. We thus studied aberrant methylation of the genes RASSF1A and CASP8 and its consequence on expression in cell lines and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Data from our laboratory show that aberrant methylation of the tumor suppressor gene RASSF1A can be found in 4 out of 6 AT/RT, and reexpression of the gene could be achieved by a combination of the demethylating agent 5-aza-2 0 -deoxycytidine and TSA. 20 In our study we find HDI highly effective towards the mentioned tumors, supporting the need for more preclinical studies especially concerning high-risk medulloblastoma, neuroblastoma and rhabdoid tumors. In a novel approach, we enclosed tumor cell lines from this entity in our investigation.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Data from our laboratory show that aberrant methylation of the tumor suppressor gene RASSF1A can be found in 4 out of 6 AT/RT, and reexpression of the gene could be achieved by a combination of the demethylating agent 5-aza-2 0 -deoxycytidine and TSA. 20 In our study we find HDI highly effective towards the mentioned tumors, supporting the need for more preclinical studies especially concerning high-risk medulloblastoma, neuroblastoma and rhabdoid tumors. In a novel approach, we enclosed tumor cell lines from this entity in our investigation.…”
Section: Discussionmentioning
confidence: 49%
“…We used RT-PCR on genes, which had previously been found epigenetically silenced in cell lines. 20 Experimental procedures have been described. 20 Primer sequences were:…”
Section: Expression Analysismentioning
confidence: 99%
“…This genetic alteration appears to be crucial in the molecular pathogenesis of most AT/RTs. 122 Mühlisch et al 105 found the aberrant methylation of the RASSF1A promotor region as having an important role in AT/RT formation and progression. The same group evaluated the effects of HDAC inhibitors in embryonal tumor cell lines demonstrating a dose-and time-dependent apoptosis.…”
Section: Atypical Teratoid/rhabdoid Tumormentioning
confidence: 99%
“…For this purpose, DNA clones representing methylated and non‐methylated bisulfite‐converted DNA at position C122 and C229 were amplified separately by PCR. Then the PCR products were mixed to obtain the theoretical methylation levels given above . These artificial samples were used to prove the key parameters of the developed analytical method, such as linearity, migration times, accuracy and precision of the recorded data sets (“proof‐of‐principle”).…”
Section: Methodsmentioning
confidence: 99%